2022
DOI: 10.3390/jcm11123314
|View full text |Cite
|
Sign up to set email alerts
|

Body Emotional Investment and Emotion Dysregulation in a Sample of Adolescents with Gender Dysphoria Seeking Sex Reassignment

Abstract: Adolescents with gender dysphoria (GD) often have internalizing symptoms, but the relationship with affective bodily investment and emotion dysregulation is actually under-investigated. The aims of this study are: (1) the comparison of Self-Administrated Psychiatric Scales for Children and Adolescents’ (SAFA), Body Investment Scale’s (BIS), and Difficulties in Emotion Regulation Scale’s (DERS) scores between GD adolescents (n = 30) and cisgenders (n = 30), (2) finding correlations between body investment and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Moreover, it is widely thought that there is an emotion-regulatory function of self-harm, and several research results support the existence of an emotion dysregulation trait among people who engage in these behaviors, which could decrease the perception of negative affect in many different ways: both intrapersonal, arising from within a person, and/or interpersonal [21]. In adolescents with GD a bidirectional link between low protective attitudes towards one's body and greater di culty in regulating emotions seems to exist [20] considering that they must learn to control emotions in adaptive ways to promote social functioning and psychological well-being despite social rejection, stigma, discrimination, violence and victimization, low access to health care providers experienced in transgender health, and limited availability of a multidisciplinary team of experts [55,56].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, it is widely thought that there is an emotion-regulatory function of self-harm, and several research results support the existence of an emotion dysregulation trait among people who engage in these behaviors, which could decrease the perception of negative affect in many different ways: both intrapersonal, arising from within a person, and/or interpersonal [21]. In adolescents with GD a bidirectional link between low protective attitudes towards one's body and greater di culty in regulating emotions seems to exist [20] considering that they must learn to control emotions in adaptive ways to promote social functioning and psychological well-being despite social rejection, stigma, discrimination, violence and victimization, low access to health care providers experienced in transgender health, and limited availability of a multidisciplinary team of experts [55,56].…”
Section: Discussionmentioning
confidence: 97%
“…It is known that emotion dysregulation acts as a transdiagnostic factor of vulnerability for multiple psychiatric disorders [35]. Adolescents experiencing gender incongruities are exposed to a greater emotional burden than cisgender ones, both because of the increased social pressures they face and the complex maturation of their emotional regulation skills [20]. Although previous research has indicated that individuals with an early onset of GD could experience higher distress than individuals with a late onset which are usually older and potentially better at coping with distress [17], our results agree with more recent literature data and could support the idea that adolescents who experience gender incongruence later in time probably have fewer opportunities to adapt to such emotional and social burden [21,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madeddu et al (2009) found a 22% prevalence of Cluster B personality disorders, characterized by outbursts of anger and impulsivity. Moreover, a recent study on adolescents with GD described a link between negative emotional investment in the body and broader difficulties regulating and managing negative emotions (Petruzzelli et al, 2022). Of note, a study by Lingiardi et al (2017), which applied the SWAP-200 to a sample of GD individuals, identified a histrionic/extroverted personality subtype characterized by emotional impulsivity, theatrical behavior, and lack of empathy, while also linking this personality profile to self-image stability, identity coherence, and body satisfaction.…”
Section: Emotional Dysregulation Within Eating Disorders and Gender D...mentioning
confidence: 99%
“…This expansion prompted extensive studies on this construct in relation to mental health issues. Previous research has established connections between body investment factors and suicide risk, distinguishing between suicidal and non-suicidal individuals [2][3][4], the onset of depressive symptoms [5], non-suicidal self-injury behaviors [6], and acting as a mediator between emotion dysregulation and gender dysphoria in adolescents [7]. Additionally, it has been associated with physical health conditions; studies post-surgery have indicated that wound dehiscence negatively impacts body investment [8].…”
Section: Introductionmentioning
confidence: 99%